2021
DOI: 10.1155/2021/5512174
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Adsorption of Methylene Blue and Methyl Orange by UiO-66-NO2 Nanoparticles

Abstract: In this work, the adsorptive removal of methylene blue and methyl orange by UiO-66-NO2 nanoparticles was studied. The influence of pH on the adsorption capacity was assessed. The kinetics of the adsorption process were investigated and compared with pseudo-first-order, pseudo-second-order, Elovich, and intraparticle models. The kinetics of the adsorption fits moderately with the pseudo-first-order, but perfectly fits with pseudo-second-order models, and has a very good fit with the Elovich and intraparticle mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 48 publications
0
11
0
1
Order By: Relevance
“…13 Wastewater discharged during cationic dye manufacturing and dyeing can cause allergic dermatitis, neurological diseases, rashes, cancer, and mutations. 14 The positively charged cationic dye molecule is soluble in water and creates colored cations in the solution. Wastewater from printing and dyeing processes frequently contains the cationic dye neutral red (NR).…”
Section: Introductionmentioning
confidence: 99%
“…13 Wastewater discharged during cationic dye manufacturing and dyeing can cause allergic dermatitis, neurological diseases, rashes, cancer, and mutations. 14 The positively charged cationic dye molecule is soluble in water and creates colored cations in the solution. Wastewater from printing and dyeing processes frequently contains the cationic dye neutral red (NR).…”
Section: Introductionmentioning
confidence: 99%
“…This shows that, degree of CBB adsorption by OTAuAgNPs is proportionate to the CBB concentration and follows the PSO and Elovich model, con rming the chemisorption of dyes on nanoparticle surfaces. Adsorption of methyl orange by UiO-66-NO 2 nanoparticles also tted PSO and Elovich model which con rmed the chemisorption interaction among the dye and the nanoparticle surface (Dinh et al,2021). The rate constant of the process was observed as 5.96E -04 g/mg.min.…”
Section: Adsorption Kineticsmentioning
confidence: 74%
“…Studies conducted byBello et al (2009) indicated that the adsorption of MBD on the surface of periwinkle shells had a maximum theoretical Qe value of 454 mg/g (which is lower than the value obtained in this study). K2 values had a range of 0.015 to 0.0124 g/(mg/h) and the fitness was described by R 2 as approximately equal to 0.99 Dinh et al (2021). also obtained k2 = 0.064 g/mg/min for the adsorption of MBD by UiO-66-NO2 nanoparticles, which obeyed a pseudo second order kinetic.The adsorption data for MBD onto CaONPO did not fit the pseudo first order model but obeyed the pseudo second order model with R 2 value of 0.9735.The third kinetic model considered for the adsorption of methylene blue dye is the Elovich model, which can technically be represented according to equation 9(Goyal et al 2021) 𝑢𝑛𝑖𝑡 = 𝑔/𝑚𝑔 and 𝛼 (𝑈𝑛𝑖𝑡 = 𝑚𝑔/𝑔.…”
mentioning
confidence: 74%